Disabling Pansclerotic Morphea Of Children - Chakravarty Jagadih; Coondoo Arijit; Benerjee Raghubir (Wolters Kluwer Medknow Publications, 2001)
A case of disabling pansclerotic morphea in a female child of 9 years with unusual involvement of the digits is reported.